Un relámpago en la noche : interpretación de la relación entre temporalidad, amor y tiempo en F. W. J. Schelling - Garrido-Maturano, Ángel E. (2003)
First, the article distinguishes, in Schelling´s philosophy, successivity and extaticoriginary temporality, and contends that the latter can be conceived as co-temporalization. Secondly, an analysis of loveis advanced as an experience in which co-temporalization is consummated, and it is shown how in the erotic pathos, through an empathic movement of overdetermination, the ecstases are sublated as such and “condensed" in an instant of eternity. Finally, the author differentiates temporality and the real-actual time that Schelling conceives as the continuity of discontinuous temporalities. Special attention is payed to the importance of Schelling´s thought for the current discussion on time.